Reconciling immersion and presence: Locative game mechanics and narrative techniques for cultural heritage. Issue 1 (1st June 2018) - Haahr, Mads
Locative gaming dates back to the early 2000s, and with the success of Ingress (2012) and Poke´mon GO (2016), locative games have now entered the mainstream in a very serious way. However, while the genre holds considerable promise for cultural heritage, it has yet to make a real impact for this purpose. A particular challenge is to reconcile the two apparently conflicting concerns of ensuring immersion into the experience without compromising the audience's sense of presence in the physical space. For example, Ingress and Poke´mon GO offer excellent immersion in the gameplay but at the cost of near-total loss of the player's sense of presence in the physical environment, even to the extent that accidents occur. For cultural heritage, presence is not only about safety but also about the audience experiencing the site and not only the digital content. In this article, we argue that for locative games to be successful for cultural heritage, they must bridge the design tension between offering immersion and presence. We use two of our own titles to shed light on the design concerns and show how careful use of locative game mechanics and narrative techniques can help reconcile these two design pressures and create a new type of engagement with cultural heritage.